Attitudes of Dental Students towards the Prescription of Antibiotics during Endodontic Treatment - Lauzan haj Khalaf; Salma Kabbaj; Babacar Toure (MDPI AG, 2024)
Aim: This study aimed to evaluate the antibiotic-prescribing attitudes of dental students during the management of endodontic infections. Materials and methods: This study was conducted in the five faculties of dental medicine in Morocco. A self-administered questionnaire was used and completed online. This questionnaire has three parts: the first includes the socio-demographic data, the second is related to the types of antibiotics prescribed, and the final addresses clinical scenarios in which antibiotics are prescribed. Data were analyzed with Jamovi, and X2 and ANOVA tests were performed. Results: Three hundred and sixty-five students participated in this study. The average duration of antibiotic therapy was 5.87 ± 1.45. Of all the students, 83.8% prescribe amoxicillin first. For patients with penicillin allergy, clindamycin was the most prescribed, amounting to 53.9%. Antibiotics are prescribed for all pulp and periapical pathologies. For acute pulpitis and acute apical periodontitis, a statistically significant difference between the different faculties was noted (p = 0.03). Regarding apical abscesses, antibiotic prescription was more frequent at the public faculty of Casablanca, corresponding to 92.8%. (p = 0.02). Conclusion: It appears from this study that there is a need for faculties to develop innovative teaching models to improve students' level of knowledge on antibiotics and their indications in endodontics.